Neoantigens combined with in situ cancer vaccination induce personalized immunity and reshape the tumor microenvironment - Kuanhan Feng; Xinru Zhang; Jiale Li; Mingzhi Han; Jinghuang Wang; Fucai Chen; Zhiwen Yi; Liuqing Di; Ruoning Wang (Nature Communications)
Abstract Neoantigen (nAg) vaccines can induce anti-tumor specific immunity, and tumor killing promotes further antigen diffusion, which is expected to improve prognosis. However, the mutation of cancer cells under the selective pressure of vaccines and the immunosuppressive tumor microenvironment make the therapeutic effect unsatisfactory. Here, we develop a nanovaccine (nAg-MRDE/Mn) that can deliver nAg and induce in situ cancer vaccination to synergistically promote a personalized immune response, enhance antigen diffusion, and improve the microenvironment by modulating immunosuppressive cells and activating the innate immune response. Experiments show that nAgs are presented by dendritic cells and expressed by T cells, which cooperate with in situ vaccination to stimulate specific immunity. Cells involved in immunosuppression, such as M2 macrophages and regulatory T cells, are down-regulated, while M1 macrophages and natural killer cells are increased. In addition, the hydrogel loaded with chemokines and nAg-MRDE/Mn inhibits postoperative tumor recurrence, and the combination of nAg-MRDE/Mn and αPD-1 improves the therapeutic effect of αPD-1. This study validates the clinical potential of this strategy and provides ideas for improving neoantigen vaccines.